A Comparative Study On The Antidiabetic Effect Of Nelumbo Nucifera And Glimepiride In Streptozotocin Induced Diabetic Rats - POLURU RAKESH,; DR.D. SATHISH SEKAR,; DR K. L. SENTHIL KUMAR, (International Journal of Pharma and Bio Sciences, 2011)
The present study is aimed to evaluate the anti diabetic effect of Nelumbo nucifera rhizome and flower extracts on serum glucose level in normal and streptozotocin induced diabetic rats. The various extracts was prepared and screened for their effects on serum glucose level in rats. In streptozotocin induced animals the various extracts showed significant anti diabetic property. From the result of these studies, we can conclude that the Nelumbo nucifera rhizome and flower extract is a promising anti diabetic agent.